(untitled) (Research, Society and Development, 2022)
The objective of this article is to verify the importance of participatory democratic management in the identification of determining factors in the management processes of the PDDE, based on a bibliographic review of articles published in the period from 2000 to 2020. An exploratory methodology was used. , with a qualitative approach and bibliographic-documentary strategy. 48 articles published in the analyzed period were identified. The analysis of the articles allowed us to identify four determining factors: Training, Participatory Management, Social Control and Resource Management and Autonomy. The results of the analysis are fundamental in defining monitoring policies aimed at mitigating the difficulties of the PDDE management processes. Democratic and participatory management is complex, especially in a program of national scope, which involves different social actors, whose performance is influenced by various institutional, economic, political, social and cultural factors. The results of the study can help to conduct future studies on each of the determining factors identified.